Geopolitics of Rare Earth Elements: A Descriptive Analysis from the National Security and Defense Framework - Jorge Alfonso García Torres (Estudios en Seguridad y Defensa, 2025)
The geopolitics of Rare Earths Elements (REE) has emerged as a strategic axis for national security and defense. In Colombia, this topic is incipient and has a limited academic production. A review of indexed databases like Scopus, Web of Science, and Science Direct revealed a lack of scientific studies on security and experimental approaches. This study, of an exploratory nature, is based on three pillars: (1) analysis of national and international background on the geopolitics of REE, with emphasis on the China-US dynamics; (2) application of the approach neo-functionalist and the theory of the natural resource curse to interpret the phenomenon; (3) correlation between the presence of these minerals in Colombia and critical socioeconomic variables. The findings demonstrate the need for a national strategy to manage and protect these strategic resources.